2018
DOI: 10.1155/2018/8073679
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal and Cytotoxic Activities of Polyphenol Extracts fromSolanum tuberosumspp.tuberosumand spp.andigenaCultivars onEscherichia coliand Human Neuroblastoma SH-SY5Y CellsIn Vitro

Abstract: Potatoes (Solanum tuberosum L.) are a good source of dietary antioxidant polyphenols. This study investigated the potential antioxidant, bactericidal, and cytotoxic activities in vitro of the phenolic compounds present in tubers of one S. tuberosum spp. tuberosum (Summerside), and three S. tuberosum spp. andigena (landraces Moradita, Waicha, and Santa María) cultivars. Both the content of phenolic acids, chlorogenic acids (CGAs) being the most abundant, and the antioxidant activity were higher in extracts from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 45 publications
(60 reference statements)
2
16
0
Order By: Relevance
“…Furthermore, these evidences support the suitability of these feedstock to be valorized as new products in a circular economy viewpoint. S. tuberosum peelings have previously investigated as potential source of new crude glycoalkaloid [ 58 ], polyphenolic [ 59 ], and polyphenolic/anthocyanin [ 60 ] antimicrobials. In addition, these natural compounds are characterized by a low persistence in the environment (the half-live of α-solanine has been estimated to vary in the range 1.8–4.1 days at 15 °C), features that makes them suitable for the field application in a perspective of ecofriendly control of plant disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these evidences support the suitability of these feedstock to be valorized as new products in a circular economy viewpoint. S. tuberosum peelings have previously investigated as potential source of new crude glycoalkaloid [ 58 ], polyphenolic [ 59 ], and polyphenolic/anthocyanin [ 60 ] antimicrobials. In addition, these natural compounds are characterized by a low persistence in the environment (the half-live of α-solanine has been estimated to vary in the range 1.8–4.1 days at 15 °C), features that makes them suitable for the field application in a perspective of ecofriendly control of plant disease.…”
Section: Discussionmentioning
confidence: 99%
“…Moradita, Waicha, and Santa María potato cultivars were selected based on previous work from our laboratory (Silveyra et al, 2018) and other groups (Calliope et al, 2018). The skin and flesh colors are purple and yellow for Moradita, pink and yellow for Waicha, and intensely red for Santa María.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we studied the cytotoxic effect of Andean potato polyphenol extracts against human neuroblastoma and hepatocarcinoma cell lines. Treatments resulted in a dose-dependent viability reduction in all cell types (Martínez et al, 2018; Silveyra et al, 2018). However, we do not know which compound(s) exert(s) these biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…The study of [ 20 ] also revealed that the extracts of some pigmented potatoes were lethal against the hepatocarcinoma (Hep3B) cell lines. Silveyra et al [ 65 ] also showed that the skin and flesh extracts of some cultivars possessed some antibacterial properties against E. coli . These authors reported that the skin possessed more activities than the flesh extracts.…”
Section: Pigmented Potato Biological Activitymentioning
confidence: 99%